Esophageal stents for less invasive treatment of mediastinitis - Safranek, Jarmil; Geiger, Jan; Vesely, Vladimir; Vodicka, Josef; Treska, Vladislav (Wideochirurgia i inne techniki maloinwazyjne, 2014)
INTRODUCTION: In spite of the progress in diagnosis and therapeutic options, esophageal perforation resulting in mediastinitis is a very serious condition with a high morbidity. AIM: To evaluate the use of esophageal stents for the treatment of patients suffering from mediastinitis. MATERIAL AND METHODS: Retrospective (2008-2012) analysis of a group of patients requiring surgical treatment. The evaluation was focused on the cause of perforation, stent type and its parameters, the surgical method used, duration of stenting and total length of treatment. RESULTS: In total, 16 patients were treated by stenting. All patients were treated with the stent being placed across the defect in the esophagus. Mediastinitis was accessed and drained with the aid of a thoracotomy or thoracolaparotomy (8 cases), or using a combination of a laparotomy/laparostomy and pleural drainage (5 cases). The most basic interventions were either pleural or external cervical drainage (3 and 1 cases, respectively). One patient, in whom a stricture had developed at the healed perforation, was subjected to esophageal resection. Four patients died. The average period that the stent was left in situ was 53.7 days. The average period of hospitalization of those patients who survived was 53.4 days. CONCLUSIONS: Using stents in therapy neither increased survival (mortality of 25%), nor decreased the length of therapy of patients once mediastinitis had developed. The main advantage of stenting is the preservation of the native esophagus and the reduced extent of surgical mediastinal drainage.
Keywords: mediastinitis; esophageal stent; esophageal perforation